2018
DOI: 10.3390/v10030110
|View full text |Cite
|
Sign up to set email alerts
|

Are microRNAs Important Players in HIV-1 Infection? An Update

Abstract: HIV-1 has already claimed over 35 million human lives globally. No curative treatments are currently available, and the only treatment option for over 36 million people currently living with HIV/AIDS are antiretroviral drugs that disrupt the function of virus-encoded proteins. However, such virus-targeted therapeutic strategies are constrained by the ability of the virus to develop drug-resistance. Despite major advances in HIV/AIDS research over the years, substantial knowledge gaps exist in many aspects of H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
70
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(74 citation statements)
references
References 309 publications
(363 reference statements)
1
70
0
Order By: Relevance
“…There are two key mechanisms by which miRNAs can confer antiviral activity (57)(58)(59). Through a direct-mechanism, miRNAs can inhibit viral protein translation by targeting HIV-1 mRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…There are two key mechanisms by which miRNAs can confer antiviral activity (57)(58)(59). Through a direct-mechanism, miRNAs can inhibit viral protein translation by targeting HIV-1 mRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…The means by which HIV manages to evade the host's immune strategies involves the reshaping of the host cells with the aid of viral accessory proteins and RNA (Fruci et al, 2017). However, while host miRNAs can play either positive or negative roles in viral replication and disease evolution (Balasubramaniam et al, 2018), the existence of viral miRNAs has only relatively recently been demonstrated and their role in pathogenesis is still disputed (Omoto et al, 2004).…”
Section: Microrna Signaling In Hiv Infectionmentioning
confidence: 99%
“…For instance, cellular miR-17 promotes the stability and translation of viral RNA by targeting the 3 -UTR of RNA viruses (Scheel et al, 2016). The latter affects virus replication by targeting host cellular mRNAs (Balasubramaniam et al, 2018). For example, miR-200b and miR-429 suppress the expression of zinc finger E-box binding homeobox 1 (ZEB1) and zinc finger E-box binding homeobox 2 (ZEB2), the two cellular proteins that have key roles to establish and maintain latent infections of Epstein-Barr virus, thus leading to lytic reactivation of latently infected cells (Ellis-Connell et al, 2010).…”
Section: Discussionmentioning
confidence: 99%